2018
DOI: 10.1590/0037-8682-0442-2017
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life predictors for people living with HIV/AIDS in an impoverished region of Brazil

Abstract: Introduction: Quality of life (QoL) is important for people living with HIV/AIDS, particularly as the disease progresses. This study evaluated the QoL of people living with HIV/AIDS (PLWHA), as well as its predictors, in one of the most impoverished regions of Brazil. Methods: This cross-sectional study was conducted with patients older than 18 years with HIV/AIDS from two specialized HIV/AIDS care centers in the city of Montes Claros between 2013 and 2014. Sample size was calculated considering the estimates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 17 publications
0
8
0
8
Order By: Relevance
“…Higher education can also lead to better understanding of the disease and thus the higher QOL (34,45,46). Yet, two studies in Brazil reported no significant correlation between the education level and the dimensions of the QOL (44,47).…”
Section: Resultsmentioning
confidence: 99%
“…Higher education can also lead to better understanding of the disease and thus the higher QOL (34,45,46). Yet, two studies in Brazil reported no significant correlation between the education level and the dimensions of the QOL (44,47).…”
Section: Resultsmentioning
confidence: 99%
“…The patients with a low QoL had the characteristics of being under 44 years of age, women, not working (so they had a low income), and having a low clinical status. The low clinic status included problems with their lungs, fever, pain, depression, and CD4 counts <500 µ/l (Ferreira, Teixeira, Silveira, & Carneiro, 2018). Other studies have also shown the same thing, namely that the majority of patients with HIV and AIDS have a good QoL.…”
Section: Quality Of Lifementioning
confidence: 84%
“…Malnutrition is the condition that occurs when the body does not get enough nutrients [38]. This is determined based on the body mass index (BMI), which can be measured as weight in kilograms divided by the square of height in meters (kg/m 2 ).…”
Section: Outcome Measuresmentioning
confidence: 99%